Etika Periklanan: Studi Kasus Iklan Mie Sedaap Versi Tasty Beef Yakiniku - Alya Salsabilla; Assya Putri Sanggita; Salsa Hijriyatin Nisa; Daniel Handoko (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Advertising ethics regulate advertising practices to ensure that advertisements delivered to consumers are accurate, honest, and not misleading. Unethical or inappropriate advertising can harm consumers by providing false or misleading information, which can ultimately damage brand reputation and consumer trust. The approach used in this study is a qualitative approach using a case study method on the Sedaap noodle advertisement, Tasty Beef Yakiniku version. The results of the study showed that there were violations of the Indonesian Advertising Ethics (EPI) that were not yet known by many people, so that they could mislead consumers who watched them. Advertisers must pay attention to norms, regulations, customs and traditions in producing advertisements so that unwanted incidents do not occur and also do not offend the community affected by the advertisements made to avoid controversy among the community